Rectus sheath single-injection blocks: a study to quantify local anaesthetic absorption using serial ultrasound measurements and lidocaine serum concentrations. (27th May 2019) - Primrose, Matthew; Al Nebaihi, Hamdah; Brocks, Dion R; Widder, Sandy; Fairey, Adrian; Tsui, Ban; Dillane, Derek; Green, James S
Abstract: Objectives: Rectus sheath blocks are an established option for analgesia following abdominal surgery, but pharmacokinetic data are limited. This study sought to characterise the absorption of lidocaine injectate and the pharmacokinetics of lidocaine after rectus sheath injection. Methods: Bilateral rectus sheath single-injection blocks were given to 10 patients undergoing general or urological surgery. Afterwards, serial lidocaine serum levels and ultrasound measurements of the rectus sheath injectate reservoir were collected. Key findings: Injectate within the rectus sheath was visible with ultrasound up to 12 h after injection. However, the rate of drug absorption exceeded that of injectate disappearance. Peak serum concentration occurred within 30 min with average peak concentrations of 1.65 μg/ml. Lidocaine clearance was lower than reported in young healthy subjects. The body mass index positively correlated with lidocaine terminal phase half-life, and clearance negatively correlated with age. Conclusions: The study provides the first data describing lidocaine pharmacokinetics after rectus sheath injection. Peak serum concentrations transiently achieved systemic levels associated with pain relief after a single bolus injection. The data from this study could be used to develop a regime using single shot rectus sheath blockade with a bolus of lidocaine followed by infusion using bilateral rectus sheath catheters.